Prospects for the development of national logistics under sanctions - A. S. Tikhonova; D. S. Shikhalieva; N. A. Davydova; G. I. Popova (Путеводитель предпринимателя)
The article examines the theoretical background and practical experience of creating a logistics startup in the context of the national logistics infrastructure. The purpose of this scientific article is to develop a system of recommendations for implementing a logistics startup in conditions of economic turbulence. The relevance of the stated topic is due to the fact that due to international instability of economic relations, a significant part of the logistics export and import channels have collapsed, which requires entrepreneurial initiative to create new supply channels taking into account current foreign economic realities. At the same time, in the current conditions, the problems of the Russian logistics system related to its lack of self–sufficiency and the presence of certain links, the existence of which is necessary to ensure its integrity, have become urgent. In particular, these links are represented by structures providing container transportation, structures authorized to carry out international insurance and technology companies used in organizing navigation and dispatch processes. The high probability that Russia will be cut off from global logistics processes for a long time indicates that there are unfilled niches in the country for the creation of domestic logistics start–ups, which requires the implementation of logistics start–ups on conditions other than standard market ones.